Underwater endoscopic submucosal dissection and hybrid endoscopic submucosal dissection as rescue therapy in difficult colorectal cases - Paolo Cecinato; Matteo Lucarini; Chiara Campanale; Francesco Azzolini; Fabio Bassi; Romano Sassatelli (Endoscopy International Open, 2022)
Background and study aims Colorectal endoscopic submucosal dissection (ESD) is still not widely used due to its technical difficulty and the risk of complications. Rescue therapies such as hybrid ESD (H-ESD) have been proposed for very difficult cases, as has underwater ESD (U-ESD). This study evaluated the safety and efficacy of H-ESD and U-ESD in difficult cases. Patients and methods The hospital charts of consecutive patients referred for colorectal ESD between January 2014 and February 2021 because they were considered difficult cases were retrospectively analyzed. The primary outcome of the study was en bloc resection rate; secondary outcomes were the rate of complete resection, procedure speed, and incidence of adverse events (AEs). Results Fifty-nine colorectal neoplasms were considered, 22 of which were removed by U-ESD and 37 by H-ESD. The en bloc resection rate in the U-ESD group was 100 %, while it was 59.5 % in the H-ESD group. Dissection speed was 17.7mm2/min in the U-ESD group and 8.3 mm2/min in the H-ESD group. The AE rate was low in the U-ESD group and moderately high during H-ESD (5 % and 21.6 %, respectively; and perforation rate 0 % and 10.8 %, respectively). Larger lesions were treated with U-ESD, while more fibrotic ones were treated with H-ESD. Conclusions U-ESD and H-ESD are both effective and safe techniques in difficult colorectal situations. U-ESD is particularly effective and fast for large lesions when it is not possible to obtain comfortable knife position, while H-ESD is more suitable for very fibrotic lesions.